Production of quality planting material of horticultural crops: a boon for farmers - Trivedi, A K; Verma, S K (Indian Horticulture, 2019)
Availability of quality planting material is one of the most important elements of successful horticultural production. Planting material available to smallscale farmers in different areas particularly in Central Himalayan Region is often of inferior quality, which undermines potential yield and performance of crops. Raising the quality planting material locally to be used by local farmers is itself a challenge. Therefore, awareness and technical knowledge for production of planting material of horticultural crops may transform economy of farmers in this region.